Vivências de formação leitora com alunos do 9º ano na Escola Francisca Leite Vitorino em Boa Vista - PB - Melo, Marília Félix Diniz (2020)
This research deals with a literary education experience developed in a 9th grade class of Elementary School, from the Municipal School Professora Francisca Leite Vitorino, in Boa Vista-PB, from the reading of the stories “Olhos D'água” by Conceição Evaristo and “Felicidade Clandestina” by Clarice Lispector, aiming at the formation of the reader from the perspective of literary literacy. To this end, it was intended to promote reading and writing experiences, through the elaboration and development of a Basic Sequence in the model suggested by Cosson (2018), in order to encourage critical thinking through discussions, conversation circles and reflections in the classroom. Finally, we proposed the creation of Reading Diaries (RD), to streamline the writing process and the critical formation of the reader, in the light of the literary perspective, since this methodological tool favors reflection on the themes conveyed in reading and intertextuality, present in the composition of the textual / literary genre used. Our interest was to carry out a project with practices that would provide the intellectual growth of the target audience: 30 students, aged between 13 and 17 years old. In this context, we insert methodologies, guided by other conceptions of reading such as, for example, act and production of meaning, to make the student a competent and potential reader, aware, able to read, reflect and act critically in society and capable of, in a process of otherness, putting oneself in the place of the other, to reflect on the world, both from the discussions and reflections in the classroom, as well as from the construction of the Reading Diaries. Among the theoretical framework to support the discussions, stand out Brasil (2017), Colomer (2007), Machado (2005), among others. Methodologically, our study is classified as an action research, with a qualitative approach. From the experience of the interventional methodologies, described here, we saw the relevance of bringing texts to the dynamics of student participation and involvement, in the search for interaction and expansion of the discussions that the reading and writing process can provide. Far beyond what we expected, expectations regarding student participation and involvement were met, that is, at each stage, we saw how much they were dedicated and contributed to the classes and the implementation of the suggested activities. In this sense, the results pointed to a representative involvement and self-identification, on the part of the students, through the literary readings they performed in the classroom, taking into account the subjectivity of the notes and the moments of sharing, reflections, dialogues and understandings underlying the texts.